(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aims to determine the role played by the media in shaping the political culture of the university youth in the Faculty of Arts and Humanities at Damascus University, as well as to monitor the differences in the level of political influences resulting from exposure to the media with different variables (gender, political affiliation. Due to the nature of the research, the methodology used is the scientific method based on the description and analysis. The method used in the research is the method of social survey in the sample, in addition to relying on the questionnaire as the main tool for collecting data and information. Third and fourth year students from the Faculty of Arts and Humanities at Damascus University from the academic year 2018/2019. The research has reached a set of results, the most important of which are: 1. There are differences in the level of effects of exposure to media by gender. 2.There are no differences in the level of effects of exposure to the media according to the variable of political affiliation. 3. There is a correlation between the level of media exposure and the political influences of the university youth in the Faculty of Arts and Humanities at Damascus University. يهدف البحث إلى تحديد الدور التي تقوم به وسائط الإعلام في تشكيل الثقافة السياسية لدى الشباب الجامعي في كلية الآداب والعلوم الإنسانية في جامعة دمشق, وكذلك رصد الفروق في مستوى التأثيرات السياسية الناتجة عن التعرض لوسائط الإعلام باختلاف متغير (الجنس, الانتماء السياسي). ونظراً لطبيعة البحث، فإن المنهج المستخدم هو المنهج العلمي القائم على الوصف والتحليل، أما الطريقة المستخدمة في البحث فهي طريقة المسح الاجتماعي بالعينة, بالإضافة إلى الاعتماد على الاستبيان كأداة رئيسية لجمع البيانات والمعلومات, واختيرت العينة بطريقة العينة العشوائية البسيطة, والتي تكونت من 433 مفردة من طلاب السنتين الثالثة والرابعة من كلية الآداب والعلوم الإنسانية بجامعة دمشق من العام الدراسي 2018/2019. وقد توصل البحث إلى مجموعة من النتائج أهمها: • توجد فروق في مستوى التأثيرات الناتجة عن التعرض لوسائط الإعلام باختلاف متغير الجنس. • لا يوجد فروق في مستوى التأثيرات الناتجة عن التعرض لوسائط الإعلام باختلاف متغير الانتماء السياسي, • هناك علاقة ارتباطية بين مستوى التعرض لوسائط الإعلام والتأثيرات السياسية لدى الشباب الجامعي في كلية الآداب والعلوم الإنسانية في جامعة دمشق.